PENGARUH STRATEGI INOVASI TERHADAP KINERJA OPERASIONAL INDUSTRI BATIK DI YOGYAKARTA - Utami, Yekti (Universitas Muhammadiyah Magelang, 2009)
The aim of this research is to examine the effect of innovation strategy to operational performance of batik industry in Yogyakarta. Dimensions of innovation strategy are leadership orientation (being a leader or follower), types of innovation (process and product), source of innovation (internal and external), implementation of innovation and investment level. Operational performance measured by using productivity, defect of production volume, warranty claims cost, quality cost and delivery in full on time to consumers. The research use sequential model which suggest a causal sequence among dimensions of innovation strategy that will influence the operational performance. The data in this research collected through direct survey in selected company and there are 86 companies qualified for sample. Data processing conducted with regression. The result of this research indicates direct and indirect significant effect among the dimensions of innovation strategy to the operational performance. Leadership orientation gives significant effect to process innovation, product innovation, internal source, external source, implementation of innovation, investment level and operational performance. Product innovation, internal source and implementation of innovation give significant effect to the investment rate. Process innovation and external source do not give significant effect to the investment level.